2004
DOI: 10.1007/s10108-003-0078-7
|View full text |Cite
|
Sign up to set email alerts
|

Stock market cycles and stock market development in Spain

Abstract: In this paper we use Spanish stock market data to identify the bull and bear phases of the market and to analyze its characteristics during the period . We compare these characteristics with those of the US and of two other European countries (Germany and the UK). Our sample is divided in two subperiods in order to account for differences induced by the process of development undergone by Spanish capital markets in the late 1980's and early 1990's. We find that the Spanish stock market has become increasingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Many empirical papers have studied stock market volatility during bull and bear periods. A number of authors have found that volatility is higher during bear markets than in bull periods, including Maheu and McCurdy (2000), Edwards et al (2003), Gomez-Biscarri and Perez de Gracia (2004), Jones et al (2004), Gonzalez et al (2005), Guidolin and Timmermann (2005), Nishina et al (2006), Tu (2006), etc. On the other hand, persistence is highly related with volatility.…”
Section: Introductionmentioning
confidence: 98%
“…Many empirical papers have studied stock market volatility during bull and bear periods. A number of authors have found that volatility is higher during bear markets than in bull periods, including Maheu and McCurdy (2000), Edwards et al (2003), Gomez-Biscarri and Perez de Gracia (2004), Jones et al (2004), Gonzalez et al (2005), Guidolin and Timmermann (2005), Nishina et al (2006), Tu (2006), etc. On the other hand, persistence is highly related with volatility.…”
Section: Introductionmentioning
confidence: 98%
“…The other group of researchers believes that for a period to be deemed a bull (bear) market, the stock market price should increase (decrease) over a substantial period of time. For instance, the stock market price should rise (fall) over a period of longer than 5 months to denote a distinct bull (bear) market phase (see Pagan and Sossounov 2003, Biscarri and de Gracia 2004, Gonzalez et al 2005, Kaminsky and Schmukler 2008. Since there is no unique definition of bull and bear markets, there is no single preferred method to identify the state of the stock market.…”
Section: Dating Of Bull and Bear Market Statesmentioning
confidence: 99%
“…1. For example, Assoe (1998) investigates regime switching behaviour of nine emerging markets and finds that these emerging market returns and volatilities change significantly over time in response to government policies, productivity switches or capital market reforms. Biscarri and de Gracia (2004) identify the bull and bear phases of Spanish stock market and find that the process of financial development, such as capital market opening, financial liberalization or integration processes, affects the Spanish stock market behaviour significantly.…”
Section: Notesmentioning
confidence: 99%